Comparison of early and delayed EUS-guided drainage of pancreatic fluid collection - Chantarojanasiri, Tanyaporn; Yamamoto, Natsuyo; Nakai, Yousuke; Saito, Tomotaka; Saito, Kei; Hakuta, Ryunosuke; Ishigaki, Kazunaga; Takeda, Tsuyoshi; Uchino, Rie; Takahara, Naminatsu; Mizuno, Suguru; Kogure, Hirofumi; Matsubara, Saburo; Tada, Minoru; Isayama, Hiroyuki; Koike, Kazuhiko (Endoscopy International Open, 2018)
Background and study aims While endoscopic ultrasound (EUS)-guided drainage of pancreatic fluid collection (PFC) is recommended to be performed ≥ 4 weeks after onset of acute pancreatitis (AP), early (< 4 weeks) interventions are needed in some symptomatic cases. Despite feasibility of early percutaneous drainage, there have been few studies about early EUS-guided drainage of PFC.Patients and methods Consecutive patients who received EUS-guided drainage (EUS-PCD) of infected or symptomatic PFC at the University of Tokyo were retrospectively studied. Contraindications for EUS-PCD are lack of encapsulation or adhesion to the gastrointestinal tract. Safety and effectiveness of early vs delayed (≥ 4 weeks) EUS-PCD were compared.Results A total of 35 patients underwent EUS-PCD (12 early and 23 delayed) using 19 large-bore fully-covered metallic stent and 16 plastic stents. The median diameter of PFC was 110 mm (40 – 180) and 122 mm (17 – 250) in the early and delayed drainage groups, respectively. Median time from onset of AP to drainage was 23 and 85 days for early and delayed drainage, respectively. The technical success rate of EUS-guided drainage was 100 %. Endoscopic necrosectomy was performed in six early and 16 cases of delayed drainage. The adverse event rate was 25 % (3 bleeding) and 13 % (2 perforations and 1 CO2 retention) in the early and delayed drainage groups, respectively. Two patients died (1 early and 1 delayed) due to multiorgan failure. Conclusion Endoscopic drainage and subsequent necrosectomy of symptomatic PFC within 4 weeks after onset of acute pancreatitis was feasible, given that the collection was encapsulated and attached to the gastrointestinal tract.